Opportunities and Challenges in Implementing Regional Public Service Agency Policy in Regional Hospitals: Systematic Review - Masyitoh Basabih; Indriaswari Widhakuswara (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
The Policy of the Regional Public Service Agency (Badan Layanan Umum Daerah or BLUD) is a form of autonomy for Regional Public Hospitals (Rumah Sakit Umum Daerah or RSD) born from healthcare service reforms. Despite being implemented for over two decades, several challenges in persist policy implementation. This research aims to analyze the opportunities and challenges in implementing the BLUD policy in RSD within the context of public services. The research method employed is a systematic review using inclusion criteria. Searches were conducted using the keywords policy implementation, BLUD, and RSD, utilizing the Garuda database and Google Scholar. This systematic review analyzes articles published from 2007 to 2022. The study identifies challenges such as resource quality, organizational fragmentation, and suboptimal communication. On the other hand, there is evidence of positive acceptance or response from implementers towards the BLUD policy. Based on the analysis, it can be concluded that the BLUD policy provides opportunities for RSD to enhance performance through its flexibility. Human resource capacity and communication pose challenges in BLUD policy implementation within RSDs. Implement targeted training programs for both regional governments and hospitals should address the specific needs and challenges of BLUD implementation, such as potential knowledge gaps arising from differing educational backgrounds.